Why do Mandarin speakers code-switch? A case study of conversational code-switching in China - Zhong, Xinyi; Ang, Lay Hoon; Sharmini, Sharon (Springer Nature, 2024)
Multilingualism is becoming increasingly common worldwide, with multilingual studies becoming more popular and accelerating interpersonal language contacts; however, it remains controversial and ambiguous in China. The current study aims to explore code-switching (CS) patterns and factors among Mandarin-dominated mainland Chinese speakers and investigate multilingual development in China through CS, as it is a multilingual practice. Conversational analysis was conducted to analyse daily interactions in short videos posted online, categorise language varieties and frequencies, identify CS patterns, and examine the factors influencing CS patterns. The results revealed that foreign languages and dialects other than Mandarin were spoken by Mandarin-dominated speakers. Three of four CS patterns were also pinpointed regarding language practices in China. Insertion was the most predominant pattern, followed by backflagging and alternation. The CS patterns employed by Mandarin-dominated mainland Chinese speakers were influenced primarily by participant-related factors, followed by linguistic-related factors, sociopsychological factors, convenience, and situational factors. The prevalence of the insertional CS pattern and the influence of personal factors suggest that China’s Mandarin-speaking community is in an early phase of multilingual development.